Analisis Pengaruh Bakteri Rhizobium SP terhadap Petumbuhan Sengon di Lahan Bekas Tambang Kapur - Ratu Salma Aqilla; M. Akbari Danasla (Pusat riset dan Inovasi Nasional, 2025)
The land of the former Pit B limestone mine of PT Semen Baturaja has failed to plant and grow dwarf plants at several locations due to low nutrient content, such as Nitrogen, Phosphorus, Potassium, Soil PH, C-Organic, and cation exchange capacity (KTK). This condition causes the plant not to grow optimally. This study aims to determine the effect of the application of Rhizobium sp bacteria on the growth of Sengon plants (Falcataria moluccana) using polybag media on the land. The method used was an experiment with the treatment of giving Rhizobium sp in various doses. The results of the study showed that the administration of Rhizobium sp had a real effect on increasing the growth of sengon plants. Based on laboratory observations and analysis, there is a change in soil pH from slightly alkaline to neutral after treatment. The C-Organic content increased from medium to very high, while the Nitrogen content rose from medium to high. The elements of Phosphorus, Potassium, and KTK have also increased significantly and are classified as very high. The best treatment is obtained at a dose of 30 grams of Rhizobium sp, which gives optimal results on an increase in plant height and root length. These findings suggest that the application of Rhizobium sp can be an effective biotechnology alternative in post-mining land rehabilitation, particularly in improving soil fertility and forestry crop productivity. This research contributes to environmental management and the use of microorganisms in the restoration of degraded ecosystems.